경영자 과잉투자 성향이 실제이익조정에 미치는 영향 - 변설원; Seol-Won Byun (디지털정책학회지, 2025)
This study empirically analyzes the impact of managerial overinvestment propensity on real earnings management (REM). Overinvestment can lead to inefficient resource allocation and deteriorate financial soundness, which may incentivize managers to engage in REM to present a more favorable financial position. Using a sample of 19,187 firm-year observations from non-financial firms listed on the Korea Exchange between 2003 and 2019, the study finds that managers with a high overinvestment propensity actively utilize REM. In particular, abnormal cash flow adjustments and reductions in selling and administrative expenses are prominent REM strategies. These findings suggest that managers with a strong overinvestment propensity may prefer REM to highlight short-term performance and maintain the trust of external stakeholders. 본 연구는 경영자의 과잉투자 성향이 실제이익조정(REM)에 미치는 영향을 실증적으로 분석하였다. 과잉투자는 기업의 자원 배분 비효율성을 초래하고 재무 건전성을 저하시킬 수 있으며, 이에 따라 경영자는 재무제표를 긍정적으로 보이기 위해 REM을 활용할 가능성이 크다. 2003년부터 2019년까지 한국 증권거래소 상장 비금융업 기업 19,187 기업-연도를 대상으로 분석한 결과, 과잉투자 성향이 강한 경영자는 REM을 적극적으로 활용하며, 특히 비정상적인 현금흐름 조정과 판매관리비 절감을 통한 이익조정이 두드러졌다. 이는 과잉투자 성향이 높은 경영자가 단기 성과를 부각하고 외부 이해관계자의 신뢰를 유지하기 위해 REM을 선호할 수 있음을 시사한다.